ASSOCIATION BETWEEN AGE AND NUMBER OF MISSING TEETH BASED ON DMFT INDEX AMONG PATIENTS VISITING A PRIVATE DENTAL HOSPITAL - Komal Labh, Ankita; L. , Leelavathi; Mani, Geo (International Journal of Psychosocial Rehabilitation, 2020)
Aim: A variety of factors like poor oral hygiene, susceptibility of tooth morphology towards cariogenic bacteria, etc., lead to tooth loss. In this study, an attempt was made to find an association between missing teeth based on the DMFT index and age of the study participants.Materials and methods: A retrospective cross-sectional study was conducted in the year 2020 using patient records from the Department of Public Health Dentistry, Saveetha Dental College, Chennai, after reviewing and analyzing the data from patient records between June 2019 and March 2020. Microsoft Excel® was used to tabulate the data. Data was then exported to the Statistical Package for Social Sciences (SPSS) for Windows (Version 19, 2010) for further analysis. A chi-square test was done to find an association between age and number of missing teeth based on the DMFT index score. Results: The total sample size was 4730. Sample had a gender distribution of 54.3% males and 45.7% females. The sample consisted of 46.1% of 18-35 year olds, 42.8% of 36-55 year olds, and 11.1% of 56+ year olds. 1-7: No. of teeth were missing mostly in 18-35 year olds; 8-14 and 22-28: No. of teeth were missing mostly in 36-55 year olds; and 15-21: No. of teeth were missing mostly in 56+ year olds.Conclusion: Within the limits of the study, it can be concluded that based on DMFT index, the highest possible number of missing teeth (22-28) were seen in above 56-year-old study participants